Machine Time: Unifying Chronos and Kairos in an Era of Ubiquitous Technologies. - Gallagher, John R. (Rhetoric Review)
Chronos and kairos are often understood as separate from one another in discussions of rhetorical temporality. For online and other highly mediated contexts, however, chronos and kairos can be understood as deeply related and intertwined. Via the concept of transduction, this article introduces machine time, which describes rhetorical time across a broad range of digital contexts, including online discussion forums and computer code.